Pemberdayaan Perempuan Melalui Pemanfaatan Limbah Kulit Nanas Menjadi Lilin Aromatik di Desa Menanti Selatan, Kecamatan Kelekar, Kabupaten Muara Enim: Penelitian - Anisa Ulandari; Dumyati; Dwi Larasati; Etri Aiza; Muhammad Andhika Fajar Ardiansyah; Octarika Rahmadianti; Ekis Sagita; Inda Maharani (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Women's empowerment in Menanti Selatan Village, Kelekar District, Muara Enim Regency, is hindered by abundant yet neglected pineapple peel waste, while productive-age women lack access to creative economy training. This study aims to optimize the waste into aromathic candles to enhance skills, economic independence, and sustainable business prospects. Employing a qualitative approach via Participatory Action Research (PAR), the population of productive women (150 individuals) was purposively sampled to 35 participants. Instruments included participatory observation, semi-structured interviews, and questionnaires; data analysis used Miles and Huberman model with triangulation. Findings reveal heightened waste awareness as economic resources, production skills yielding Rp10,000–Rp20,000 profit margins per unit, social solidarity through WhatsApp groups, and organic waste reduction. The conclusion affirms the model's effectiveness for replication in pineapple-producing villages, despite limitations in sample scale and digital marketing.